CONTINUING EDUCATION: MANDATORY ACTION FOR GRADUATE PROFESSORS (Fiep Bulletin - online, 2014)
This study agrees with the fact that teacher training needs to compulsorily take a prominent position in discussions related to public policies, in order to reveal the obvious need for changes to be implemented, more effectively, in teacher training policy, as well as in researches and publications in the area and in debates about the initial and continuing training of teachers. This paper aims to highlight, in a systematic and effective way, the importance of continuing education for teachers who have completed an undergraduate, when executing this methodological practice in the setting of professional teaching. This study is a qualitative research, sparked by systematic literary bibliographic review in scientific journals, articles in the SciELO database. As selection criteria, it was considered items with bibliographic data that addressed the importance of continuing education for teachers, published between 2005 and 2012. The results of the data analyzed in the study make it clear that the teacher's work is a permanent and very complex challenge, in which the educator must have had a solid initial education and also a continuous training to complement and update, permanently, this professional teacher, which does not mean, however, that continued education is built solely through the accumulation of courses, but also that it must have a close and essential relationship with the empirical practice of everyday life experienced only in school. It is noticed that the assignment of value characterization means something to continuing education, since this enables the development of necessary skills for teachers' professionalization, supplying, in a way, the lack of professional skills, related to competencies, where a great number of current educators are found.
Keywords: Education; Professionalization; Learning